Anaerobic biodegradation, physical and structural properties of normal and high-amylose maize starch films - Weiwei, Liu; Juan, Xue; Beijiu, Cheng; Suwen, Zhu; Qing, Ma; Huan, Ma (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: Biodegradable plastics have attracted considerable attention in recent years due to their biodegradability, biocompatibility and non-toxicity. In this study, normal maize starch (containing 25% amylose) and high-amylose maize starch (containing 80% amylose) were served as model materials to prepare starch/polyvinyl alcohol (PVA) blends. To comprehensively study the effects of amylose contents on the film performances, the mechanical properties, water resistance and anaerobic biodegradability of the two films were examined. Moreover, the processes of anaerobic degradation were investigated by evolutions of biogas production, pH in reactors and the changes of film structures and compositions. The results indicated that amylose content played an important role in the microstructures of starch film as well as mechanical properties and water resistance, whereas it had no significant influence on anaerobic biodegradability of the films. Nonetheless, the structure of high-amylose maize starch/PVA film was more suitable and beneficial to the anaerobic biodegradation than that of the normal maize starch/PVA film, because it could effectively avoid accumulation of volatile fatty acids, which contributed to the stable biogas production, short fermentation period and non-souring in the reactor. Keywords: maize starch film, anaerobic biodegradation, polyvinyl alcohol(PVA), amylose content, biopolymer DOI: 10.3965/j.ijabe.20160905.2005 Citation: Liu W W, Xue J, Cheng B J, Zhu S W, Ma Q, Ma H. Anaerobic biodegradation, physical and structural properties of normal and high-amylose maize starch films. Int J Agric & Biol Eng, 2016; 9(5): 184-193.